Library Collection Development Policies. Training Piloting Module N0:8 (Confluenţe Bibliologice, 2017)
The author reports about the training on Pilot Module No. 8 „Library Collection Development Policy" for the library staff. Training took place at the USARB Scientific Library within the framework of ERASMUS+ LNSS Project "Library Network Support Services: Modernizing Libraries in Armenia, Moldova and Belarus through Library Staff Development and Reforming Library Services". The training was attended by European partner universities, Angela Repanovici, PhD, professor, University "Transilvania", Brasov, Romania, and Dr. Manolis Koukourakis, Director of the Library of the University of Crete.
Keywords: collections development policy; Erasmus+ programme; international projects; LNSS project